The accuracy of a novel 3D digital evaluation method of intraoral fitness for removable partial dentures. (May 2022) - Yoon, Jung-min; Liu, Yunsong; Liu, Yushu; Sun, Yuchun; Ye, Hongqiang; Zhou, Yongsheng
Abstract: With the development of three-dimensional (3D) scanning and measurement technologies, the internal adaptation of restorations was measured by the 3D analysis method. The purpose of this study was to explore a novel 3D digital evaluation method to assess the intraoral fitness of removable partial dentures (RPDs) and evaluate the accuracy of this novel digital method in vitro. A 3D digital method to evaluate the clinical fitness of RPD was introduced. A standard stone cast of a partially edentulous mandible simulating the oral tissues and a corresponding RPD were used to evaluate the accuracy of this novel digital method (3D analysis on duplicated polyether cast) and another reported 3D digital evaluation method (3D analysis on RPD directly) for intraoral fitness of RPD in vitro. 12 polyvinyl siloxane (PVS) replica specimens were fabricated in each method in vitro, and the thicknesses of these PVS replicas were measured by 3D analysis on duplicated polyether cast (named Polyether group), 3D analysis on RPD directly (named Denture group), and 3D analysis on the stone cast (named Stone group), respectively. The thicknesses of PVS replicas were compared with analyses of variance (ANOVA) to evaluate the accuracy of these methods (α = 0.05). The accuracy based on the mean thickness of the PVS replicas of Polyether group were better than that of Denture group (P < 0.05) and had no statistical difference with that of Stone group (P > 0.05). 3D analysis on duplicated polyether cast has comparable trueness and precision to 3D analysis on the stone cast and is feasible for evaluating clinical fitness of RPD. Highlights: Introduce a novel 3D digital evaluation method to assess the intraoral fitness of removable partial dentures (RPDs) and evaluate the accuracy of this novel digital method in vitro. Evaluate the trueness and precision of this novel digital method (3D analysis on duplicated polyether cast) and another reported 3D digital evaluation method (3D analysis on RPD directly) for intraoral fitness of RPD in vitro, compared with a precise method that can only be used in vitro. The novel 3D digital evaluation method (3D analysis on duplicated polyether cast) we explored could be used to evaluate the clinical intraoral fitness of RPD which has similar trueness and precision compared with that of 3D analysis on the stone cast.